Language control in bilingual language comprehension: evidence from the maze task - Wang, Xin (Frontiers in Psychology, 2015)
Most empirical evidence on switch costs is based on bilingual production and interpreted as a result of inhibitory control. It is unclear whether such a top-down control process exists in language switching during comprehension. This study investigates whether a non-lexical switch cost is involved in reading code-switched sentences and its relation to language dominance with cross-script bilingual readers. A maze task is adopted in order to separate top-down inhibitory effects, from lexical effects driven by input. The key findings are: 1) switch costs were observed in both L1-L2 and L2-L1 directions; 2) these effects were driven by two mechanisms: lexical activation and inhibitory control; 3) language dominance modulated the lexical effects, but did not affect the inhibitory effects. These results suggest that a language control mechanism is involved in bilingual reading, even though the control process is not driven by selection as in production. At the theoretical level, these results lend support for the Inhibitory Control model during language switching in comprehension; while the BIA/BIA+ model needs to incorporate a top-down control mechanism to be able to explain the current findings.